2018
DOI: 10.3390/molecules23071799
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Different Sensitization Patterns of MRSA to Antibiotics Using Electroporation

Abstract: Treatment of bacteria-associated infections is complicated and antibiotic treatment alone is often inadequate to overcome biofilm infections. Physical methods allow overcoming this problem and propose solutions that are non-dependent on drug resistance. In this work, we investigated the feasibility of pulsed electric fields for sensitization of MRSA to common antibiotics. We analyzed the efficacy of inactivation of methicillin-resistant Staphylococcus aureus in 5–20 kV/cm electric field separately and in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
3
10
0
Order By: Relevance
“…As it can be seen in Figure 3-left, electroporation can be effectively used for protein extraction; moreover, different electroporation parameters affect the protein yield. As expected, electroporation protocol 32 × 100 µs, 20 kV/cm, 1 Hz most strongly affected bacterial viability (Figure 3-right) due to higher energy input (379 kJ/L) (Novickij et al, 2018). Nevertheless protein yields were lower compared to electroporation protocol where lower energy of the pulses was applied -65 kJ/L (8 × 100 µs, 20 kV/cm, 1 kHz), which suggests that the risen temperature during the treatment possibly damaged proteins.…”
Section: Comparison Of Extraction Of Proteins By Means Of Electroporasupporting
confidence: 75%
“…As it can be seen in Figure 3-left, electroporation can be effectively used for protein extraction; moreover, different electroporation parameters affect the protein yield. As expected, electroporation protocol 32 × 100 µs, 20 kV/cm, 1 Hz most strongly affected bacterial viability (Figure 3-right) due to higher energy input (379 kJ/L) (Novickij et al, 2018). Nevertheless protein yields were lower compared to electroporation protocol where lower energy of the pulses was applied -65 kJ/L (8 × 100 µs, 20 kV/cm, 1 kHz), which suggests that the risen temperature during the treatment possibly damaged proteins.…”
Section: Comparison Of Extraction Of Proteins By Means Of Electroporasupporting
confidence: 75%
“…It seems that the reason for this phenomenon is the ability of amphotericin B [46] and aminopenicillins [47] to interfere with the integrity of the cellular structures and a disintegration-dependent increase in uptake of 3-BP into microbial cells. An analogous mechanism of sensitizing bacterial cells to antibiotics has been proven against methicillin-resistant S. aureus exposed to electroporation [48]. In the Visca et al [26] study, the existence of an additive interaction of 3-BP with TET and chloramphenicol against S. aureus has also been demonstrated.…”
Section: Discussionmentioning
confidence: 96%
“…Also, where stated in these previous studies, the post-pulse incubation times before diluting out of the antibiotics have been as long as 24 h ( Novickij et al, 2018a ; Kuyukina et al, 2020 ; Martens et al, 2020 ). Implementation of such a long incubation for on-site hospital wastewater treatment would require a reservoir in which the undiluted antibiotic concentration would be retained until release into the communal sewage (and thus dilution), and the required reservoir volume would likely be prohibitive.…”
Section: Introductionmentioning
confidence: 96%
“…To date, the majority of studies that have combined electroporation and antibacterials [see Table 2 in Garner (2019) ] have focused on substances permissible in food and beverage processing. Still, five recent studies have quantified the potentiation of inactivation rates for combination of electroporation and clinical antibiotics ( Korem et al, 2018 ; Novickij et al, 2018a ; Vadlamani et al, 2018 , 2020 ; Rubin et al, 2019 ), with their exposure parameters and results summarized in Table 1 . Two further studies ( Kuyukina et al, 2020 ; Martens et al, 2020 ) used the disk diffusion test to study electroporation-induced increase in susceptibility of Rhodococcus ruber to five and Escherichia coli to four different antibiotics, at increasing concentrations, and confirmed that such susceptibility increases are generally achievable.…”
Section: Introductionmentioning
confidence: 99%